A General Synthetic Route to NHC‐Phosphinidenes: NHC‐mediated Dehydrogenation of Primary Phosphines. Issue 8 (26th February 2021) - Werner, Luis; Horrer, Günther; Philipp, Michael; Lubitz, Katharina; Kuntze‐Fechner, Maximilian W.; Radius, Udo
Abstract: The dehydrocoupling of primary phosphines with N ‐heterocyclic carbenes (NHCs) to yield NHC‐phosphinidenes is reported. The reaction of two equivalents of the NHCs Me2 Im (1, 3‐dimethylimidazolin‐2‐ylidene), Me4 Im (1, 3, 4, 5‐tetramethylimidazolin‐2‐ylidene), i Pr2 Im (1, 3‐di‐ iso ‐propylimidazolin‐2‐ylidene) and Mes2 Im (2, 4, 6‐trimethylphenylimidazolin‐2‐ylidene) with PhPH2 and MesPH2 led to the NHC stabilized phosphinidenes (NHC)PAr: ( i Pr2 Im)PPh (1 ), (Mes2 Im)PPh (2 ), (Me4 Im)PPh (3 ), (Mes2 Im)PMes (4 ), (Me2 Im)PMes (5 ), (Me4 Im)PMes (6 ) and ( i Pr2 Im)PMes (7 ). The reaction of t BuPH2 with two equivalents of the NHCs afforded the corresponding NHC stabilized parent phosphinidenes (NHC)PH: ( i Pr2 Im)PH (8 ), (Mes2 Im)PH (9 ) and (Me4 Im)PH (10 ). Reaction of 1 with oxygen and sulfur led to isolation of i Pr2 Im‐P(O)2 Ph (11 ) and i Pr2 Im‐P(S)2 Ph (12 ), whereas the reaction with elemental selenium and tellurium gave (NHC)PPh cleavage with formation of ( i Pr2 Im)Se (13 ), i Pr2 ImTe (14 ) and different cyclo ‐oligophosphines. Furthermore, the complexes [{( i Pr2 Im)PPh}W(CO)5 ] (15 ), [Co(CO)2 (NO){( i Pr2 Im)PPh}] (16 ) and [(η 5 ‐C5 Me5 )Co(η 2 ‐C2 H4 ){( i Pr2 Im)PPh}] (17 ) have been prepared starting from 1 and a suitable transition metal complex precursor. The complexes 16 and 17 decompose in solution upon heating to ca . 80 °C to yield the NHC complexes [Co( i Pr2 Im)(CO)2 (NO)] and [(η 5 ‐C5 Me5 )Co( i Pr2 Im)(η 2 ‐C2 H4 )] with formation of cyclo ‐oligophosphines. The reaction of 1 with [Ni(COD)2 ] afforded the diphosphene complex [Ni( i Pr2 Im)2 ( trans ‐PhP=PPh)] 18 . Abstract : The dehydrocoupling of primary phosphines with NHCs is a general and convenient synthetic approach to prepare NHC‐phosphinidenes in moderate to high isolated yield, as exemplified by the synthesis of different NHC‐phosphinidenes. The reactivity of ( i Pr2 Im)PPh (1 ) towards chalcogenides and selected transition metal complexes is presented.